2018
DOI: 10.1038/s41434-018-0006-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving therapeutic efficacy of IL-12 intratumoral gene electrotransfer through novel plasmid design and modified parameters

Abstract: The use of immunomodulatory cytokines has been shown effective in regressing a wide range of tumors. However, systemic delivery of recombinant cytokines results in serious, potentially life-threatening, adverse effects. By contrast, nucleic acid transfer via electroporation (EP) is a safe and effective method of delivering plasmid-encoded cytokines to tumors. Intratumoral delivery of IL-12 plasmid DNA by electroporation (IT-pIL12-EP) produced objective response rates in Phase 2 clinical trials in metastatic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Several reports have demonstrated the necessity for CD80 and CD86 expression on professional antigen presenting cells (APC) for T-cell activation and propagation (36)(37)(38)(39)(40). IL12 is a heterodimeric proinflammatory cytokine that induces the production of IFNg, which induces the differentiation of Th1 cells, and forms a link between the innate and adaptive immune responses (28)(29)(30). Recombinant IL12 has shown remarkable properties as an antitumor agent in preclinical models (41,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have demonstrated the necessity for CD80 and CD86 expression on professional antigen presenting cells (APC) for T-cell activation and propagation (36)(37)(38)(39)(40). IL12 is a heterodimeric proinflammatory cytokine that induces the production of IFNg, which induces the differentiation of Th1 cells, and forms a link between the innate and adaptive immune responses (28)(29)(30). Recombinant IL12 has shown remarkable properties as an antitumor agent in preclinical models (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, unlike LNP formulations, fluorophores are easily covalently attached to CART delivery vehicles (BDK-CART; McKinlay and colleagues, 2018; Benner and colleagues, 2018), which can be utilized to correlate location of transfected cells (either anatomic, or within specific cell populations) with gene expression, thus providing insight into the mechanistic basis of effective therapeutic outcomes. In this study, we utilized the BDK-CART-mRNA delivery platform to induce local expression of genes encoding the well described immunomodulatory molecules CD70 (11), OX40L (24,25), CD80 (26,27), CD86, IL12 (28)(29)(30), and IFNg (31), both individually and in combination. We used a two-tumor model to demonstrate that local administration of mRNA coding for immunomodulatory molecules can elicit a systemic response that can cure both the treated (local) and untreated (distal) tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, gene therapy with plasmid DNA / RNA vaccines have bright prospects in the prevention and treatment of various cancers. Immunization with these vaccines allows intracellular expression of the encoded immunomodulatory cytokines and can induce a strong humoral and cellular immune response dependent on B and T cells (Burkart et al, 2018; Lopes, Vandermeulen, & Preat, 2019). Despite the infusive efficacy observed in preclinical studies, DNA / RNA vaccines are limited due to the poor immune response and toxicity in humans.…”
Section: In Situ Antitumor Vaccination With Plasmid Dna/rnamentioning
confidence: 99%
“…Several approaches to deliver DNA / RNA vaccines intratumorally have been proved to be safe and effective (Brown et al, 2018; Burkart et al, 2018; Guerrero‐Cazares et al, 2014; X. Liu et al, 2011). Intratumoral delivery of interleukin‐12 (IL‐12) plasmid DNA vaccine by electroporation is the driving force of strong cellular immune responses, reversing the immunosuppressive state of melanoma (Burkart et al, 2018). A recent Phase I clinical trial demonstrated that intratumoral delivery of plasmid DNA encoding IL‐12 resulted in complete regression of melanoma in two patients with minimal systemic toxicity (Daud et al, 2008).…”
Section: In Situ Antitumor Vaccination With Plasmid Dna/rnamentioning
confidence: 99%
See 1 more Smart Citation